Improving Inclusive Students Competence through 3D Flashcard Animation-Based Animal Exploration - Hasanudin, Muhaimin; Riskinanti, Karisma; Santoso, Hadi; Novrizal, Kevin; Lestari, Mulyati; Afiyati, Afiyati (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2025)
Children with special needs often face challenges in recognizing animal shapes and sounds. This community service program (PKM), based on the Service Learning approach, developed an application called Teh Melati, which utilizes Augmented Reality (AR) by combining 3D animation with traditional 2D flashcards to aid in animal recognition. The PKM was conducted over one day with 32 students with disabilities aged 6–14 years (N=32) at HS-Lantaburo. The Service Learning methodology involved actively engaging the community (teachers, parents, and students) in the design, implementation, and evaluation of the learning intervention. Students participated in an interactive animal exploration game that focused on animal images and sounds. Pre-intervention test scores averaged 63.75, while post-intervention scores increased to 81.25. A total of 25 students (78% of the participants) showed significant improvement. The active participation of teachers and parents in hands-on workshops further extended the impact of the intervention. These results demonstrate that learning gaps in special needs education can be addressed through community involvement and the integration of 3D flashcard animation technology, with Service Learning serving as an effective framework for creating meaningful educational experiences for both the students and the community.